1996
DOI: 10.1007/s004410050631
|View full text |Cite
|
Sign up to set email alerts
|

Localization of constitutive isoforms of nitric oxide synthase in the gastric glandular mucosa of the rat

Abstract: Nitric oxide has been implicated in the regulation of blood flow, mucosal integrity and mucus secretion in the gastric mucosa. An antiserum directed against the C-terminal hexadecapeptide of rat brain nitric oxide synthase (NOS) and monoclonal antibodies to the neuronal and endothelial forms of NOS were used to establish the location of isoforms of NOS in rat gastric glandular mucosa. Antibodies to the neuronal form of NOS reacted with a band of 160 kDa on immunoblots of brain and gastric mucosa, and the addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
47
1
1

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 23 publications
8
47
1
1
Order By: Relevance
“…These observations indicate a role of NO in the regulation of epithelial cell integrity or secretion [25]. In addition, the localization of constitutive isoforms of nitric oxide synthase in the gastric glandular mucosa supported the role played by NO in gastric mucus secretion [26]. The concentrated localization of eNOS in endothelial cells of tumor tissue suggests that NO may act as part of a signaling cascade for neovascularization [11].…”
Section: Discussionmentioning
confidence: 84%
“…These observations indicate a role of NO in the regulation of epithelial cell integrity or secretion [25]. In addition, the localization of constitutive isoforms of nitric oxide synthase in the gastric glandular mucosa supported the role played by NO in gastric mucus secretion [26]. The concentrated localization of eNOS in endothelial cells of tumor tissue suggests that NO may act as part of a signaling cascade for neovascularization [11].…”
Section: Discussionmentioning
confidence: 84%
“…Neuronal nitric oxide synthase has been detected within several different types of cells of the gastrointestinal mucosa, such as the epithelium of the rat forestomach (Schmidt et al, 1992), brush cells (Kugler et al, 1994), chief cells (Fiorucci et al, 1995), and some endocrine cells (Burrell et al, 1996) and mucosecretory cells (Brown et al, 1992;Price et al, 1996;Byrne et al, 1997;Ichikawa et al, 1998;Price and Hanson, 1998). Preliminary studies investigating eNOS immunoreactivity in the gastric mucosa agree with previous reports on eNOS immunoreactivity in the rat stomach (Price et al, 1996), indicating that although eNOS was present in blood vessels penetrating the submucosa, the specialized gastric epithelial cells were eNOS negative (data not shown). It is clear from the present investigation that vagal afferent endings can be found in very close proximity to these nNOS-containing cells in the gastric mucosa; this provides an anatomical correlate of our evidence for NO released from the mucosa influencing the mechanosensitivity of mucosal vagal afferents.…”
Section: Discussionmentioning
confidence: 99%
“…The epithelial-to-neuronal communication process is very important in many areas of the body, including the bladder (Birder, 2005) and the gastrointestinal tract, and as such, the gastric epithelium is a rich source of NO. Various specialized cells within the gastric mucosa have been found to contain nNOS, including brush cells (Kugler et al, 1994), chief cells (Fiorucci et al, 1995), and some endocrine cells (Burrell et al, 1996) and mucosecretory cells (Brown et al, 1992;Price et al, 1996;Byrne et al, 1997;Ichikawa et al, 1998;Price and Hanson, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in the gastric mucosa, different studies have agreed on the high content of a calcium-dependent constitutive NOS (Whittle et al 1991) that produces NO, which is involved in maintaining mucosal integrity and regulating blood flow to the epithelium, but these studies have not agreed on the particular cell types responsible for this activity. These authors, using different techniques, have reported the production of NO by mucous (Brown et al 1992b;Price et al 1996;Byrne et al 1997;Ichikawa et al 1998;Price and Hanson 1998), chief (Fiorucci et al 1995a), or endocrine (Akiba et al 1995a;Burrell et al 1996) epithelial cell types. Furthermore, the presence of NOS has also been reported in the epithelium of the forestomach (Schmidt et al 1992) and the gastric brush cells (Kugler et al 1994) of the rat.…”
mentioning
confidence: 99%